Development of internet-based telerobotics - Mamat, Rosbi (Universiti Teknologi Malaysia, 2003)
The internet is a very fast evolving new technology, allowing people to electronically connect places that are thousands of miles apart. The internet serves mainly for information exchange. However since the launch of the first robots on the Internet in 1994, an enormous effort has been undertaken by hundreds of researchers to push this technology. Quite a number of designs and applications of the internet based telerobotic system have been implemented and launched on the internet. Some of the telerobotic systems are designed for blocks manipulation, paint painting and gardening. There has been much effort taken by UTM to be one of the main players in this area for the last few years. A lot of improvement has been achieved in the internet-based telerobotics since the first project launched in 1994. Thus, the project is carried out to achieve the objectives as: to study the latest finding in the internet based telerobotics especially the problems faced as well as the solutions; to study the existing project especially the problems faced; to identify the appropriate technology to improve the existing project; to design a new telerobotic system; and, to implement the new telerobotic system. Based on the findings, the task-oriented telerobotic system has been developed. In the system developed, the user need only to specify the task to be done by the robot and then the system will plan the path of the robot movement to complete the task. The system is found to be more user friendly, reliable, the safety of the working objects and the robot are well protected.